Analysis of Design Character and Typology of Sarawak Traditional Malay House - Adibah, Yusuf; Khairul Aidil Azlin, Abdul Rahman; Adam Andani, Mohammed (Human Resource Management Academic Research Society (www.hrmars.com), 2018)
This study was conducted to identify the design of Melayu Sarawak traditional houses and the focus of the study will present a typology of design of the roof, windows, walls and stairs. The scope of the study carried out within the area of Melayu Sarawak village of 60 houses and the traditional Melayu Sarawak were selected as the study sample. The findings are then documented in the form of drawings and sketches. Qualitative methods through observation and interviews were conducted with a cross case analysis. The software "SPSS Text Analytics for Surveys " were also used in producing model findings.